Ethical intuitionism - Huemer, Michael, 1969- (Houndmills, Basingstoke, Hampshire ; Palgrave Macmillan, 2005)
Michael Heumer defends a form of ethical intuitionism, according to which there are objective moral truths, some of which we know through a kind of immediate, intellectual awareness, and this knowledge provides us with reasons for action independent of our desires
1. Introduction -- 2. Non-cognitivism -- 3. Subjectivism -- 4. Reductionism -- 5. Moral knowledge -- 6. Disagreement and error -- 7. Practical reasons -- 8. Further objections -- 9. Conclusion
Includes bibliographical references (pages 255-296) and index
Keywords: Ethical intuitionism; Ethics; Intuition